Protokolle des Ministerrates der Zweiten Republik der Republik Österreich. Kabinett Leopold Figl I 20. Dezember 1945 bis 8. November 1949. Band 13 9. November 1948 bis 21. Dezember 1948 Bearbeitung Elisabeth Gmoser Peter Melichar Stefan Semotan - Enderle-Burcel, Gertrude; Jeřábek, Rudolf; Mueller, Wolfgang; Wohnout, Helmut (Die Protokolle des Ministerrates der Zweiten Republik Österreich, 2022)
The Edition of the Minutes of the Cabinet Meetings of the first government of Leopold Figl is an important contribution to the history of the early years of Austria's Second Republic and its political components after World War II. Vol. 13 encompasses meetings No. 132 of November 9, 1948 to No. 138 of December 21, 1948 as well as the accompanying minutes of the Wirtschaftliches Ministerkomitee. The discussions cover matters of foreign, domestic and economic policy, reconstruction and relations between the Austrian government and the four great powers. Particularly prominent are the pervasive problem of securing basic levels of nutrition for the Austrian population, the ongoing State Treaty negotiations and measures to carry out the European Recovery Program.